2022
DOI: 10.3390/children9060848
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Season Epidemic of Respiratory Syncytial Virus during the COVID-19 Pandemic: The High Burden of Child Hospitalization in an Academic Hospital in Southern Italy in 2021

Abstract: Respiratory syncytial virus (RSV) infection is the most common cause of hospitalization in young children. In the last 2 years, public health measures aimed at controlling the spread of SARS-CoV-2 have affected the epidemiology and seasonality of RSV worldwide. The aim of this descriptive retrospective observational study was to describe the characteristics of children hospitalized with RSV in an academic tertiary care hospital in Southern Italy in 2021. We also investigate the seasonal trends of RSV from 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
6
17
0
Order By: Relevance
“…Moreover, a delayed peak with increasing RSV cases was also noted in November 2021. 70 An early RSV season was detected in Finland after the lifting of PHSMs in September 2021. 71 A seasonality shift was observed in Portugal as well.…”
Section: Dovepressmentioning
confidence: 99%
“…Moreover, a delayed peak with increasing RSV cases was also noted in November 2021. 70 An early RSV season was detected in Finland after the lifting of PHSMs in September 2021. 71 A seasonality shift was observed in Portugal as well.…”
Section: Dovepressmentioning
confidence: 99%
“…The public health measures adopted against COVID‐19 pandemic significantly influenced the epidemiology of RSV [ 28 , 29 , 30 ]. This has been described in 2021, when Italy suffered a seasonal shift of RSV epidemic, with a beginning in August and a delayed peak in November [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 7 An epidemic of RSV infection took place in Europe during autumn 2021. [8][9][10][11] Data on SARS-CoV-2 infection in infants suggest that in most cases it presents as a mild disease. 12 In particular, a multicentre international study showed that only 3% of infants testing positive for SARS-CoV-2 developed symptoms consistent with bronchiolitis.…”
Section: Original Researchmentioning
confidence: 99%